2003
DOI: 10.3801/iafss.fss.7-941
|View full text |Cite
|
Sign up to set email alerts
|

Grid Flow: An Object-oriented Building Evacuation Model Combining Pre-movement And Movement Behaviours For Performance-based Design

Abstract: Methods for estimating the time required for building evacuations range from simple calculations to highly complex computer-based models. Some of these more complex models attempt to represent the pre-movement behaviour of occupants, as well as their movement behaviours and physical movement characteristics, often using detailed rule-based algorithms, or artificial intelligence techniques. The quantification of such behaviours can be obscure and the models complex to use. Other models may ignore pre-movement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 3 publications
0
40
0
Order By: Relevance
“…This has involved monitored evacuations, with video analysis of pre-movement and travel behaviours, and fire incident investigations of occupant and management behaviours, in a range of occupancy types. The results obtained, with other published data [3,4], have been used to develop behavioural scenario categories and also to develop calculation and computer simulation methods for evacuations [14]. Some actual pre-movement and evacuation times for design scenarios are presented in references [5 and 14], while further data are being compiled.…”
Section: Design Behavioural Scenariosmentioning
confidence: 99%
“…This has involved monitored evacuations, with video analysis of pre-movement and travel behaviours, and fire incident investigations of occupant and management behaviours, in a range of occupancy types. The results obtained, with other published data [3,4], have been used to develop behavioural scenario categories and also to develop calculation and computer simulation methods for evacuations [14]. Some actual pre-movement and evacuation times for design scenarios are presented in references [5 and 14], while further data are being compiled.…”
Section: Design Behavioural Scenariosmentioning
confidence: 99%
“…Some research results have confirmed that pre-movement time is a variable following a probability distribution, but the specific probabilistic distribution form is still unknown. Previous studies indicate that a Weibull distribution (Maclennan et al 1999), log-normal distribution (Bensilum, Purser 2002) or normal distribution may be suitable for characterizing pre-movement time. In this study, normal distribution is employed to characterize the pre-movement time.…”
Section: Fig 3 Heat Release Rate Curves Of Time-squared Firementioning
confidence: 99%
“…Early attempts to estimate evacuation times for building spaces based upon simple flow calculations or hydraulic computer models have largely given way to increasingly complex modelling simulations incorporating larger numbers of behavioral and physical movement parameters and their interactions [1][2][3][4][5]. These parameters are generally validated against experimental data, but it is not always easy to determine that they are adequately represented in the models.…”
Section: Introductionmentioning
confidence: 99%
“…In experimental evacuations it has been found that evacuation times for single enclosures are very dependent upon the interactions between the pre-travel activity time (PTAT) distributions of the occupants and the travel-related features determining physical movement to and through the exits [1,7,8]. (PTAT [also know as pre-movement time] consists of the interval between the time when a warning is given and that when the first move is made by an occupant towards an exit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation